Testing Is More Desirable When It Is Adaptive and Still Desirable When Compared to Note-Taking - Heitmann, Svenja; Grund, Axel; Berthold, Kirsten; Fries, Stefan; Roelle, Julian (Frontiers in Psychology, 2018)
Testing is a well-established desirable difficulty. Yet there are still some open issues regarding the benefits of testing that need to be addressed. First, the possibility to increase its benefits by adapting the sequence of test questions to the learners’ level of knowledge has scarcely been explored. In view of theories that emphasize the benefits of adapting learning tasks to learner knowledge, it is reasonable to assume that the common practice of providing all learners with the same test questions is not optimal. Second, it is an open question as to whether the testing effect prevails if stronger control conditions than the typical restudy condition are used. We addressed these issues in an experiment with N = 200 university students who were randomly assigned to (a) adaptive testing, (b) non-adaptive testing, or note-taking (c) without or (d) with focus guidance. In an initial study phase, all participants watched an e-lecture. Afterwards, they processed its content according to their assigned conditions. One week later, all learners took a posttest. As main results, we found that adaptive testing yielded higher learning outcomes than non-adaptive testing. These benefits were mediated by the adaptive learners’ higher testing performance and lower perceived cognitive demand during testing. Furthermore, we found that both testing groups outperformed the note-taking groups. Jointly, our results show that the benefits of testing can be enhanced by adapting the sequence of test questions to learners’ knowledge and that testing can be more effective than note-taking.